Conflits halieutiques en mer de Chine du Sud : impacts sur la gouvernance maritime - Eric Frécon (VertigO)
Southeast Asia and China are under the threat of a dramatic decline of the fish stocks, while halieutic resources provide most of the proteins for the littoral populations. In this context, illegal fishing is on the rise. This worrying trend raises the question of governance to address this concern, even if great and small powers are still in competition (territorial disputes, imposition of regional norms, etc.), at the local, regional and supra-regional levels. Two schools in International Relations offer paradigms to make sense and to untangle the issues. Realism highlights hidden interests beyond illegal fishing and focuses on powers, most of the time at a bilateral stage, like in Indonesia and China – echoing Buzan’s “securitisation”. However, because of the joint and bottom-up initiatives of multilateral and often non-state actors, specialised rather than generalist ones, a liberal approach based on cooperation is emerging step by step. It is time to proceed as new challenges could put at stake the people “human security” – as defined by the United nations in 1994.